The Concept of Islamic Educational Supervision in Development of Multicultural Education - Yusron, M. Ali; Qomar, Mujamil; Akhyak, Akhyak; Hosaini, Hosaini (Maharot : Journal of Islamic Education, 2025)
The aims of this research is to examine how the idea of Islamic education supervision is implemented in Senior High Schools in order to promote the growth of multicultural education. This study primarily examines the role of supervision in the School's multicultural education policies and practices, from conception to execution to assessment. This research employs the Systematic Literature Review (SLR) methodology to locate a suitable supervision framework to aid multicultural education. The study's findings suggest that the suggested supervision framework highlights the synergy between Islamic value-based supervision methods and the application of multiculturalism concepts. The three main elements of this framework are enhancing teachers' multicultural skills, creating a curriculum based on value integration, and ongoing monitoring to make sure that learning practices promote cultural harmony. This model is anticipated to establish an inclusive educational environment that is pertinent to the diversity found in Islamic educational establishments like MAN and other public schools at the same grade level.